2020
DOI: 10.5194/acp-2020-702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linking marine phytoplankton emissions, meteorological processes and downwind particle properties with FLEXPART

Abstract: Abstract. Marine biogenic particle contributions to atmospheric aerosol concentrations are not well understood though they are important for determining cloud optical and cloud nucleating properties. Here we examine the relationship between marine aerosol measurements with satellite and model fields of ocean biology and meteorological variables during the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES). NAAMES consisted of four field campaigns between November 2015 and April 2018 that aligned with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…3.3. The black carbon concentration on both flights is consistent with previously identified clean marine conditions (< 25 ng m −3 ) (Saliba et al, 2020;Sanchez et al, 2021), and similarly the observed carbon monoxide is consistent with observations made at an eastern North Atlantic research facility that is dominated by clean marine conditions (< 130 ppb) (Zheng et al, 2018) for near-surface measurements made on both flights (Figs. S2 and S3).…”
Section: Summary Of R/v Atlantis and C-130 Observationssupporting
confidence: 89%
See 3 more Smart Citations
“…3.3. The black carbon concentration on both flights is consistent with previously identified clean marine conditions (< 25 ng m −3 ) (Saliba et al, 2020;Sanchez et al, 2021), and similarly the observed carbon monoxide is consistent with observations made at an eastern North Atlantic research facility that is dominated by clean marine conditions (< 130 ppb) (Zheng et al, 2018) for near-surface measurements made on both flights (Figs. S2 and S3).…”
Section: Summary Of R/v Atlantis and C-130 Observationssupporting
confidence: 89%
“…It is also possible that the sulfate resided in smaller particles or more of the sulfate was removed through precipitation and subsequently more sulfate particles were formed via gas phase or in-cloud oxidation of SO 2 . Sanchez et al (2021) showed that organic aerosol mass is moderately correlated with in-water biological activity, while sulfate aerosol mass is only weakly correlated. They attributed the difference to the relatively short lifetime of the organic aerosol precursors like isoprene and monoterpenes (minutes to hours) versus sulfate precursors like DMS (> 1-2 d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this study, the CN Inv is generally greater than CN MBL , which suggests particle formation occurs more frequently above the MBL inversion, either in the FT or a decoupled layer above the marine boundary layer. Despite the lack of influence from continental and anthropogenic particles as condensational sinks in the SO, the presence of a small concentration of PMA particles can lead to a high total particle surface area (Cainey and Harvey, 2002;Sanchez et al, 2021;Yoon and Brimblecombe, 2002) and prevent NPF in the MBL. This is also shown in the histogram of the CN MBL /CN Inv ratio (Fig.…”
Section: Vertical Transportmentioning
confidence: 99%